Asymmetric proxy re-encryption system achievable for office user to securely sharing outsourcing data of mobile terminal - Wei HAO; Xu-an WANG; Xiao-yuan YANG; Li-qiang WU (网络与信息安全学报)
In order to realize the office users securely share encrypted data of the mobile terminal,an asymmetric cross-cryptosystem proxy re-encryption system is proposed.In this system,mobile terminals who have the limited computing power use relatively simple identity-based encryption system,while the server and office users use more complex identity-based broadcast encryption system.This system is based on the ciphertext conversion mechanism,which enables the simple IBE ciphertext of mobile terminal to be converted into the complex IBBE ciphertext by proxy while the proxy know nothing of the plaintext.The security of this scheme can be reduced to the safety of the IBE and IBBE scheme.Theoretical and experimental analysis indicate that the scheme is useful for the mobile ter-minal to consume less resources to make the fixed users share the data encrypted by mobile terminal,and it is more practical.